Old man and goats (with difficult words meanings) (Children Publication Karachi, 2000)
The story "The Old Man and the Goat" unfolds in a quaint village where an old man and his goat conduct an annual ritual. Villagers confess their sins to the old man, who symbolically feeds their written confessions to the goat. A curious boy, however, discovers the truth: the old man burns the confessions in a secret cave, signifying the cleansing of sins. The boy realizes that true redemption stems from personal reflection and growth, not from a mystical ritual. This tale underscores the importance of individual responsibility and the power of personal transformation.